The Review of Ignition and Combustion Processes for Water-Coal Fuels; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Egorov R. I. Roman Igorevich (2016, 2016)
Title screen